RAS testing of liquid biopsy correlates with the outcome of metastatic colorectal cancer patients treated with first-line FOLFIRI plus cetuximab in the CAPRI-GOIM trial. (7th August 2017) - Normanno, N; Esposito Abate, R; Lambiase, M; Forgione, L; Cardone, C; Iannaccone, A; Sacco, A; Rachiglio, A M; Martinelli, E; Rizzi, D; Pisconti, S; Biglietto, M; et al.
Abstract: Background: Liquid biopsy is an alternative to tissue for RAS testing in metastatic colorectal carcinoma (mCRC) patients. Little information is available on the predictive role of liquid biopsy RAS testing in patients treated with first-line anti-EGFR monoclonal antibody-based therapy. Patients and methods: In the CAPRI-GOIM trial, 340 KRAS exon-2 wild-type mCRC patients received first-line cetuximab plus FOLFIRI. Tumor samples were retrospectively assessed by next generation sequencing (NGS). Baseline plasma samples were analyzed for KRAS and NRAS mutations using beads, emulsion, amplification, and magnetics digital PCR (BEAMing). Discordant cases were solved by droplet digital PCR (ddPCR) or deep-sequencing. Results: A subgroup of 92 patients with available both NGS data on tumor samples and baseline plasma samples were included in this study. Both NGS analysis of tumor tissue and plasma testing with BEAMing identified RAS mutations in 33/92 patients (35.9%). However, 10 cases were RAS tissue mutant and plasma wild-type, and additional 10 cases were tissue wild-type and plasma mutant, resulting in a concordance rate of 78.3%. Analysis of plasma samples with ddPCR detected RAS mutations in 2/10 tissue mutant, plasma wild-type patients. In contrast, in all tissue wild-type and plasma mutant cases, ddPCR or deep-sequencing analysis of tumor tissue confirmed the presence of RAS mutations at allelic frequencies ranging between 0.15% and 1.15%. The median progression-free survival of RAS mutant and wild-type patients according to tissue (7.9 versus 12.6 months; P = 0.004) and liquid biopsy testing (7.8 versus 13.8 moths; P < 0.001) were comparable. Similar findings were observed for the median overall survival of RAS mutant and wild-type patients based on tissue (22.1 versus 35.8 months; P = 0.016) and plasma (19.9 versus 35.8 months; P = 0.013) analysis. Conclusion: This study indicates that RAS testing of liquid biopsy results in a similar outcome when compared with tissue testing in mCRC patients receiving first-line anti-EGFR monoclonal antibodies.